# Find the remainder when (x^{3} - 2) is divided by (x - 1). What is the remainder?

- x^{2} - 2, x^{2} - 2, -2, -1

**Solution:**

We will use the remainder theorem to find the remainder.

f(x) =(x^{3} - 2) is divided by (x - 1)

⇒ f(1) = x^{3} - 2

f(1) = (1)^{3} - 2

f(1) = 1 - 2

f(1) = -1

Thus the remainder is -1.

## Find the remainder when (x³ - 2) is divided by (x - 1). What is the remainder?

**Summary:**

Therefore, the remainder when f(x) = (x^{3} - 2) is divided by (x - 1) is -1.

Math worksheets and

visual curriculum

visual curriculum